PROFILE OF UNDERSTANDING THE CONCEPT OF MATHEMATIC SYMBOLS IN VISUAL-VERBAL REPRESENTATION OF STUDENTS CLASS IX SMPN 16 MAKASSAR - Munajah, Adam (Universitas Negeri Makassar, 2018)
This study aims to: (1) to describe the profile of mathematical concept understanding with visual symbol representation of students, (2) to describe the profile of mathematical concept understanding with student verbal symbol representation, (3) to describe the mathematical concept understanding profile with visual-verbal symbol representation students. The type of this research is descriptive research is qualitative. The subjects of this study consisted of 2 with the highest score on the comprehension test of the concept of building the curved side space. Instruments in this study are the researchers themselves as the main instrument, concept comprehension test instruments (TPK) and interviews. The results showed that: (1) subject I AK and IM II subjects from TPK test analysis based on conceptual understanding indicator; a) Redefining the concept, the subject of AK is correct and capable in answering the questions in both representations as well as the subject of IM; b) Classifying objects according to certain properties, the subject of AK and IM is capable of answering questions in both symbol representations, but the subject of AK in item 4 is weak in representing objects in visual form; c) Giving examples and non-examples of concepts, the subject of AK is less precise in answering the matter in visual representation, whereas for questions in verbal reproduction the subject of the AK is able to answer correctly, the subject of IM is able and correct to answer the problem in both representations; d) State the concept in the form of mathematical representation, the subject of AK and the subject of IM is capable and correct in answering the questions in both representations, but for the subject of AK in the interview session hinted that for number 8 or questions represented by visual symbols it is more difficult than the number 7 without pictures, unlike the IM subject which assumes that the two questions in both symbol representations are the same; e) Applying the concept in problem solving, the subject of AK and the subject IM quite understand and understand the direction of the problem, but both subjects failed to understand the basic concepts in solving the problem so that there is a fundamental kekeliriun so that the impact on the entire process and the end result